Upaya Pemerintah Daerah Dalam Meningkatkan Kualitas Pengelolaan Terminal di Kabupaten Tebo - Dedi Epriad; Ulima Harma (Dialektika Publik, 2020)
The purpose of this research to see how The Role of Local Government in Improving the Quality of Terminal Management (Study at the Office of Transportation, Communication and Information, Tebo Regency). This type of research used in this research is descriptive research with a qualitative approach. The results of this study show that the 1. The Department of Transportation, Communication and Information Technology of Tebo Regency has managed terminal quality such as establishing a terminal as an UPTD so that it can further maximize public services in the transportation sector, provide facilities to UPTD in improving the quality of terminal management, giving authority to UPTD for terminal management both in the service sector and in the area of local revenue, directing public transportation to utilize the terminal.